Capital Flows and Economic Growth across Spectral Frequencies: Evidence from Turkey - Yildirim, Nuri; Tastan, Huseyin (SAVEZ EKONOMISTA VOJVODINE, 2012)
This paper examines interactions and feedbacks between categories of capital flows and economic growth in Turkey for the 1992:01-2009:08 period. Our empirical analysis is based on a new version of the causality test of John Geweke (1982, p. 77) and Yuzo Hosoya (1991, p. 88) in the frequency domain proposed recently by Jorg Breitung and Bertrand Candelon (2006, p. 132). In addition, using standard methods in spectral analysis, we decompose the total covariance between capital flows and growth across main frequency bands and capture lead/lag interactions between them. Some of our findings are as follows: Variance decompositions over frequency bands reveal that variations in individual capital flow categories are largely concentrated over high (seasonal) frequencies. The nature of the interaction/feedback between growth and capital flows varies significantly over frequency bands and subcategories of flows. Over business cycle frequencies, two out of four subcategories of inflows, short-term external borrowings and portfolio investments on government bonds, drive growth whereas the other two components, long-term borrowings and portfolio investments on shares, are driven by growth. Furthermore, for the post-2001 financial crisis period we found significant bi-directional causality between long-term external borrowings and growth whereas portfolio investments, bond flows and short-term external borrowings do not affect growth in the long run.
Keywords: Capital flows; Causality in frequency domain; Geweke's measure of feedback; Turkey; ACCOUNT LIBERALIZATION; LINEAR-DEPENDENCE; SUDDEN STOPS; CAUSALITY; FEEDBACK; MARKETS; INFLOWS; CRISES; Business & Economics